Convening CGIAR Researchers to Build a Community of Practice on Weather-related Agricultural Insurance - Kramer, Berber (International Food Policy Research Institute, 2018)
With funding from the CGIAR research program on Climate Change, Agriculture and Food Security (CCAFS), the CCAFS Learning Platform for Agricultural Insurance participated as content partner and convened a group of CGIAR researchers with interest in agricultural insurance at the 14th International Microinsurance Conference (IMC) in Lusaka from November 6 – 8, 2018. Organized by the MunichRe Foundation in partnership with the Microinsurance Network (MiN) and the Microinsurance Technical Advisory Group of Zambia (TAG), the main conference brought together in Lusaka approximately 450 experts from around the world to discuss and identify ways of accelerating growth and economic viability in inclusive insurance for emerging markets. During this conference, the CCAFS Learning Platform for Agricultural Insurance, led by the International Food Policy Research Institute (IFPRI) and implemented in partnership with the CGIAR research program for Policies, Institutions and Markets (PIM), organized a series of networking and outreach events. The events were targeting the international insurance community, including policymakers, practitioners and CGIAR researchers with interest in research on weather-related agricultural insurance. Three events were organized. First, together with Innovations for Poverty Action (IPA), we held a matchmaking session linking researchers and insurance practitioners around key challenges in providing microinsurance. Second, CGIAR researchers met to coordinate research agendas and discuss strategies for evidence building and joint resource mobilization. Third, the CGIAR hosted a session to demonstrate the value of partnerships between the global insurance and agricultural research communities in addressing challenges to scaling agricultural insurance, with examples from CGIAR insurance initiatives.